Vulnerability Assessment of Mangroves using the Coastal Vulnerability Index in Timbulsloko Village, Sayung, Demak - Nila Munana; Rudhi Pribadi; Chrisna Adhi Suryono (Universitas Diponegoro, 2023)
The ongoing global warming is causing climate change in several regions of Indonesia, resulting in various impacts. One of these impacts affects coastal areas, namely, the rise in sea levels. The mangrove ecosystem is one of the coastal ecosystems with a crucial role in both ecological and economic aspects of life. This ecosystem is more susceptible to damage due to climate change and human activities. The purpose of this research is to determine the vulnerability level of the mangrove ecosystem, thereby serving as a reference for the rehabilitation of the mangrove ecosystem in Timbulsloko Village. The method used is descriptive exploratory, involving direct field measurements of oceanographic variables, such as salinity, substrate, and tidal data. The analysis employed was the Coastal Vulnerability Index (CVI) with scores divided into three categories: low, moderate, and high, with respective scores ranging between 0.45-2.31, 2.32-4.62, and 4.63-6.93. An analysis of the mangrove substrate was also conducted to determine the existing substrate types in Timbulsloko Village. The obtained results indicate that the salinity around the mangrove ranges from 29-30 ppt, the substrate type is characterized as mud, and the average tidal height is 1.5 m with a mixed leaning towards diurnal single tide. As a result, the vulnerability index value of the mangrove ecosystem in Timbulsloko Village is considered moderate, with a score of 3. The level of mangrove vulnerability is moderate, but sustainable management of the mangrove ecosystem is still required for the future.